Development of 96-microwell Plate Assay with Fluorescence Reader and HPLC Method with Fluorescence Detection for High-throughput Analysis of Linifanib in its Bulk and Dosage Forms - Khalil, Nasr Y.; Darwish, Ibrahim A.; Alanazi, Mamdouh; Hamidaddin, Mohammed A. (Current Pharmaceutical Analysis, 2021)
Background: Linifanib (LFB) is a tyrosine kinase inhibitor with antineoplastic activity. The existing methods for the analysis of LFB in bulk and dosage forms do not meet the requirements of quality control (QC) analysis. Objective: The present study was devoted to the development of two methods with high throughputs for determination of LFB. These methods are 96-microwell plate assay with microplate fluorescence reader (MWP-FR) and high-performance liquid chromatography with fluorescence detection (HPLC-FD). Methods: The MWP-FR assay was carried out in white opaque 96-well assay plates and the native fluorescence signals of LFB were measured at 360 nm for excitation and 500 nm for emission. In the HPLC-FD, the chromatographic separation of LFB and quinine sulphate (QS) as internal standard (IS) was performed on μ-Bondapack CN HPLC column using a mobile phase consisting of acetonitrile:water (60:40, v/v) pumped at a flow rate of 1 ml/min in an isocratic mode. The fluorescence detector was set at 350 nm for excitation and 454 nm for emission. Results: The linear ranges of the MWP-FR and HPLC-FD were 1-12 μg/well and 10-500 ng/ml, respectively. The limits of detection were 0.85 μg/well and 8.24 ng/ml for MWP-FR and HPLC-FD, respectively. Both MWP-FR and HPLC-FL methods were successfully applied for the determination of LFB in both bulk and tablets. Conclusion: Both methods have high analytical throughputs, they are suitable for use in QC laboratories for analysis of large numbers of LFB samples, and are environmentally friendly as they consume low volumes of chemicals and solvents.
Keywords: tyrosine kinase inhibitors